Macroeconomic Determinants of Automobile Sales in Indonesia: An Empirical Study in 1986-2016 - Suwinto Johan (Bina Nusantara University, 2019)
The aim of this research was to study the determinants of automobile sales in Indonesia. The automobile sales were the sales of car and motorcycle during 1986-2016. The research focused on five macroeconomics variables (exchange rate, Gross Domestic Product (GDP), growth of GDP, inflation, and interest rate). The total sample was 30 years of automobile sales in Indonesia. The researcher used the regression method with Statistical Package for the Social Sciences (SPSS) to test the research model. For a few variables, lag t-1 was used. The empirical results show that GDP and the growth of GDP have a significant influence on both car and motorcycle sales in Indonesia. The growth of GDP reaches a significant level at α < 1%. However, the exchange rate of USD to IDR, inflation, and interest rate do not influence automobile sales in Indonesia.